Adrenoleucodystrophy: a molecular genetic study in five families. Issue 11 (November 1990) - Del Mastro, R G; Bundey, S; Kilpatrick, M W
Abstract : A genetic study has been performed on five adrenoleucodystrophy families using DNA probes from Xq28. Members of each family had previously been tested for carrier status using the biochemical assay for very long chain fatty acids (VLCFAs), but several persons at risk had equivocal results. DNA analysis with four DNA probes St14-1 (DXS52), DX13 (DXS15), MN12 (DXS33), and hs7 showed no crossovers between them and the disease locus in persons who were clinically affected or had high levels of VLCFA or both. Thus, the genotypes provided by the DNA probes could be used for accurate carrier detection and prenatal diagnosis could be offered. Of the 17 at risk females with VLCFA levels in the normal (1 SD) range, five were defined as carriers and 12 were considered not to be.